War and ecology: a heuristic for exploring the environmental disruptions of armed conflict - Radunzel, Joel (Kansas State University, 2024)
The interrelationship between war and the environment is a vibrant focus of academic research across several disciplines and subdisciplines including environmental war, militarized landscapes, military geography, environmental geopolitics, environmental history, and environmental security. Moreover, the body of literature examining the war-environment relationship is growing in both volume and diversity. Yet, despite the burgeoning of warfare-environment research, the literature examining this topic remains fragmented along disciplinary lines and lacks theoretical depth, prompting calls for further inquiry and new conceptual frameworks to unify research. In this research, I build upon recent work in this area to suggest and validate a heuristic tool for war-environment research that will help other researchers contextualize their work and locate it within the broader body of war-environment literature. Recent trends in these fields have increasingly focused on the impacts that warfare exerts upon the environment, as opposed to earlier studies in which the environment more often served as a variable explaining the causes and conduct of warfare. This is a timely transition for the field, as global awareness of the environmental dangers posed by conflict continues to grow across the international community and even in the awareness and actions of military forces themselves. Moreover, the older and less active approaches to war-environment research, including the field of military geography, are regaining relevance due to the anticipated impacts of climate change upon the causes and conduct of warfare. This heuristic builds upon previous frameworks developed within the fields of military geography and warfare ecology. To validate the suggested heuristic, this research applies the tool to analyze how three past military conflicts—the Soviet liberation of Northern Norway in 1944, the American and Japanese campaigns in the Aleutians in 1942-43, and the Falklands War of 1982—have wrought lasting change on high-latitude landscapes to suggest what the ecological costs of potential future conflicts might be in these and other regions. I selected high latitude conflicts as case studies on the informed assumption that these environments are highly sensitive to even relatively small disturbances. These disturbances can affect long-lasting changes that would be harder to detect, or have shorter durations, in the warmer and more humid climates common to lower latitudes. In executing these case studies, I build upon a wide range of research that has already examined many narrow aspects of the environmental and cultural legacy of these two campaigns, including chemical, biological, geomorphological, economic, and cultural impacts. Using the heuristic tool to unify my own on-site field work examining these case studies with that of scholars who have already studied some of the environmental impacts that these conflicts incurred will validate the tool and demonstrate its value to other researchers seeking to contextualize the environmental costs of other conflicts both past and ongoing armed conflicts.
Keywords: Warfare ecology; Military geography; militarized landscapes; Environmental geopolitics; Military cartography